TINJAUAN YURIDIS PENGADAAN BARANG/JASA PADA MASA PANDEMI COVID-19 (PUTUSAN NO 28/PID.SUS-TPK/2022.PN.MDN) - Ronal Hasudungan Sianturi; Julianus Lase; Karto Simamora; Mesias Sagala (Ensiklopedia Education Review, 2023)
Since the announcement of the positive case of Covid-19 in Indonesia on March 2 2020, the government has stepped up steps to handle procurement of government goods and services amid the global Covid-19 pandemic. Presidential Decree No. 4 of 2020 orders all Ministries to act quickly, precisely, centrally and simultaneously. Provision of services and goods to accelerate the reduction of the virus. This is stated in the legal basis for the provision of services and goods, as stated in regulation.bpk.go.id/ (2018) Presidential Decree No. 16 of 2018 concerning the Implementation of Government services and goods. Based on Article 59 of Presidential Decree No. 59., Government agency Number 16 of 2018 (LKPP) No. 13 of 2018 concerning the Implementation of Government services and goods for Emergency Response. (SE Head of LKPP) Interpretation No 3 of 2020 concerning the Implementation of Provision of services and goods for Pandemic Efforts. The purpose of this research is to find out the implementation of services and goods during the Covid-19 pandemic. Study the Policy Institute for the Implementation of Government goods and services. Learn more about the steps taken by the ministry to accelerate the delivery of services and goods. The technique used to collect data is the use of literature studies, but also used legal materials. The data analysis used is prescriptive data analysis. The research theory used is the theory of the implementation of government services and goods during a pandemic, namely the Ministry to do it quickly, precisely, focused, and coordinated.